PELAYANAN PRIMA PRAMUSAJI DALAM MELAYANI TAMU DI RESTORAN HOTEL - Putri Sinta Belia Sinta Belia; Yen Polisda (Akademi Pariwisata Bunda Padang, Sumatera Barat, Indonesia, 2022)
This article reports the research results in the service excellence of waiters and waitresses working at hotel restaurants. The data were gained through documentation and participant observation at Cerenti Restaurant The ZHM Premiere Padang city, the province of West Sumatera, Indonesia. The findings identified that there were 18 standard procedures for servicing domestic guests or Indonesian Guests and 20 standard procedures for servicing international guests. It was also found out that there were 2(two) additional services given to international guests, that is, serving welcoming bread and offering wine. The finding of this study also stressed that all waiters and waitresses already served all guests, either domestic or international guests, appropriately as written in Standard Operating Procedures (SOP) established by Food and Beverage service.